Influência de copolímeros de estireno-butadieno e de fibras de Wollastonita na hidratação, reologia e comportamento mecânico a altas temperaturas de pastas dúcteis de cimento Portland - Vitorino, Fabrício de Campos (2017)
The present thesis focuses on the evaluation of rheological behavior, the hydration and the mechanical behavior of ductile cement paste, developed to withstand temperatures up to 300ºC. Aiming to enhance pastes thermal stability, high silica fume content was employed. To achieve higher stress and strain capacity, contents up to 36,1% of two types of wollastonite were used. SBR and carboxylated SBR (XSBR) latex copolymers were used in contents ranging from 2.1 to 5.9% to attain lower elastic modulus and increase strain capacity of the pastes. A tailored rheology protocol was employed to follow the structure rebuilding energy and fundamental rheological parameters of the polymeric and wollastonite pastes. The influence of each mixture components on the cement hydration was studied by isothermal induction calorimetry, thermal analysis and X-ray diffraction. Later, the mechanical behavior of the pastes was investigated under compression and tensile tests. The results show that, the additions of the copolymers and wollastonites to cement pastes, leaded to acceptable rheological behavior, significantly influenced the cement hydration kinetic and formed products, and lead to enhanced thermal stability, higher strength capacities, ductility and lower elastic modulus of the cement pastes.